Estimating discharge coefficient of semi-elliptical side weir using ANFIS - Dursun, O. Faruk; Kaya, Nihat; Firat, Mahmut (Elsevier, 2012)
A labyrinth weir is defined as a weir crest that is not straight in planform. The increased sill length provided by the semi-elliptical labyrinth side weirs effectively reduces upstream head to the particular discharge. They can therefore be used to particular advantage where the width of a channel is restricted and a weir is required to pass a range of discharges with a limited variation in upstream water level. In this study, the discharge capacity of semi-elliptical side weirs is estimated by using Adaptive-Neuro Fuzzy Inference System (ANFIS). 675 Laboratory test results are used for determining discharge coefficient of semi-elliptical labyrinth side weirs. The performance of the ANFIS model is compared Multiple Linear Regression (MLR) and Nonlinear Regression (NLR) models based on performance evaluation parameters. Comparison results indicated that the ANFIS technique could be successfully employed in modeling discharge coefficient. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Side weir; Discharge coefficient; Labyrinth; Semi-elliptical; Channel flow; ANFIS